O uso de jogos e material concreto no ensino de geometria espacial - Fizzon, Luciano Mateus (2018)
The work developed with the use of playful materials plays a fundamental role in the teaching and learning of Mathematics, especially in the field of Spatial Geometry, carried out with high school classes. The didactic sequence based on Didactic Engineering, was used as a form of investigation, and a posteriori analysis was carried out, which shows that learning from the use of concrete materials gives students a greater assimilation of mathematical content. The activities carried out in this work are also intended to improve teacher practice, being an important tool in the construction of meaningful learning, to be used in other moments in the classroom.